Evaluation of the repeatability of a sports technique using selected kinematics quantities based on the example of back handspring - Omorczyk, J.; Nosiadek, L.; Puszczalowska-Lizis, E.; Ambrozy, T.; Mucha, Dawid.; Bujas, P.; Mucha, Darius (Baltic Journal of Health and Physical Activity, 2017)
Background: The aim of the study was to determine the changes that occur during a back handspring performed by artistic gymnastics competitors on the basis of selected biomechanical quantities. Material/Methods: The case study included five masterclass artistic gymnastics competitors. The activities were recorded at the frequency of 120 [Hz]. Using the SkillSpector computer software, selected biomechanical variables of the back handspring technique were analyzed. The coefficient of variation was used to evaluate the variability of movement, which, in turn, was used to describe the repeatability of the back handspring technique. Results: Kinematic analysis of the back handspring carried out with the recorded video material enables the qualitative evaluation of the repeatability of the sports technique. The position of the center of mass on the vertical axis determined at borderline points of phases in the back handspring technique was the quantity of highest repeatability. The lowest repeatability was observed in the absolute and relative (movement rhythm) durations of particular phases. Conclusions: It is possible to master the back handspring while maintaining full repeatability of some biomechanical quantities characterizing the movement technique. The assessment of movement repeatability in gymnastics requires further research, with the simultaneous analysis of various biomechanical quantities and a determination of the best methods of comparison.